How high frequency food diaries can transform understanding of food security - Bell, Andrew Reid; Roberts, Mari A.; Grace, Kathryn L.; Morgan, Alexander; Tamal, Md. Ehsanul Haque (IOP Publishing, 2021)
Globally, around 2 billion people are affected by moderate to severe food insecurity. The linkages from food security through to environmental sustainability are well established, but not yet well measured. This is a critical gap, as it hampers our understanding of how environmental shocks carry through to become consumption shocks to households, communities, or regions; how responses to these shocks (e.g., dietary substitutions) feed back into further environmental stress. In this study, we present preliminary results from an innovative approach that could transform conventional practices of measuring food consumption into data on the same temporal and spatial footing as environmental data. We developed an alternative approach to conventional one-off food consumption measures that harnesses the expanding presence of mobile and smartphones, measuring food consumption over time with precision and with the potential to capture seasonal shifts in diet and food consumption patterns. Our method provides a picture of breaks and booms in access to forms of food calories, and the ability to compare different moments in time, such as those before and after a nutrition or other economic intervention, a key priority area for research and humanitarian decision-making in nutrition. We show that the distribution of food calories over time is a stronger prediction of health outcomes than any one period's measure, as might be obtained in a conventional household survey, and discuss the part that methods like this should play in a future reimagination of rural engagement and social data collection.